Mesenchymal stem cell extracellular vesicles mitigate vascular permeability and injury in the small intestine and lung in a mouse model of hemorrhagic shock and trauma. Issue 3 (March 2022) - Barry, Mark; Trivedi, Alpa; Pathipati, Praneeti; Miyazawa, Byron Y.; Vivona, Lindsay R.; Togarrati, Padma Priya; Khakoo, Manisha; Tanner, Heather; Norris, Philip; Pati, Shibani
Abstract : BACKGROUND: Hemorrhagic shock and trauma (HS/T)-induced gut injury may play a critical role in the development of multi-organ failure. Novel therapies that target gut injury and vascular permeability early after HS/T could have substantial impacts on trauma patients. In this study, we investigate the therapeutic potential of human mesenchymal stem cells (MSCs) and MSC-derived extracellular vesicles (MSC EVs) in vivo in HS/T in mice and in vitro in Caco-2 human intestinal epithelial cells. METHODS: In vivo, using a mouse model of HS/T, vascular permeability to a 10-kDa dextran dye and histopathologic injury in the small intestine and lungs were measured among mice. Groups were (1) sham, (2) HS/T + lactated Ringer's (LR), (3) HS/T + MSCs, and (4) HS/T + MSC EVs. In vitro, Caco-2 cell monolayer integrity was evaluated by an epithelial cell impedance assay. Caco-2 cells were pretreated with control media, MSC conditioned media (CM), or MSC EVs, then challenged with hydrogen peroxide (H2 O2 ). RESULTS: In vivo, both MSCs and MSC EVs significantly reduced vascular permeability in the small intestine (fluorescence units: sham, 456 ± 88; LR, 1067 ± 295; MSC, 765 ± 258; MSC EV, 715 ± 200) and lung (sham, 297 ± 155; LR, 791 ± 331; MSC, 331 ± 172; MSC EV, 303 ± 88). Histopathologic injury in the small intestine and lung was also attenuated by MSCs and MSC EVs. In vitro, MSC CM but not MSC EVs attenuated the increased permeability among Caco-2 cell monolayers challenged with H2 O2 . CONCLUSION: Mesenchymal stem cell EVs recapitulate the effects of MSCs in reducing vascular permeability and injury in the small intestine and lungs in vivo, suggesting MSC EVs may be a potential cell-free therapy targeting multi-organ dysfunction in HS/T. This is the first study to demonstrate that MSC EVs improve both gut and lung injury in an animal model of HS/T. Abstract : Mesenchymal stem cells extracellular vesicles were found to decrease vascular leak and histologic injury in the small intestine and lung in a mouse model of hemorrhagic shock and trauma, likely though systemic immunomodulation and vascular endothelial protection.Supplemental digital content is available in the text.